2017
DOI: 10.1556/2006.6.2017.031
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alcohol expectancy and intake on slot machine gambling behavior

Abstract: Background and aimsAlthough alcohol intake and gambling often co-occur in related venues, there is conflicting evidence regarding the effects of alcohol expectancy and intake on gambling behavior. We therefore conducted an experimental investigation of the effects of alcohol expectancy and intake on slot machine gambling behavior.Methods Participants were 184 (females = 94) individuals [age range: 18–40 (mean = 21.9) years] randomized to four independent conditions differing in information/expectancy about bev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Unlike drink-driving, risk-taking in gambling appears most commonly associated with financial and social, as opposed to, physical harms (Clark, 2015). Nevertheless, gambling is a behaviour that is frequently linked with alcohol consumption (Ellery & Stewart, 2014), an occurrence which is seemingly exploited via the strategic placement of slot machines in public houses, and alcohol availability in casinos (Sagoe et al, 2017). It is perhaps for similar reasons that gambling tasks are one of the more widely used measures to assess alcohol-related risk-taking behaviour, as probabilities are easily manipulated and the level of risk quantitatively assessed.…”
Section: Whisky To Riskymentioning
confidence: 99%
“…Unlike drink-driving, risk-taking in gambling appears most commonly associated with financial and social, as opposed to, physical harms (Clark, 2015). Nevertheless, gambling is a behaviour that is frequently linked with alcohol consumption (Ellery & Stewart, 2014), an occurrence which is seemingly exploited via the strategic placement of slot machines in public houses, and alcohol availability in casinos (Sagoe et al, 2017). It is perhaps for similar reasons that gambling tasks are one of the more widely used measures to assess alcohol-related risk-taking behaviour, as probabilities are easily manipulated and the level of risk quantitatively assessed.…”
Section: Whisky To Riskymentioning
confidence: 99%
“…Experimental studies measuring effects of alcohol administration on laboratory gambling have found increases in risky and/or persistent gambling (e.g. Ellery and Stewart, 2014;Cronce and Corbin, 2010;Phillips and Ogeil, 2010;Ellery et al, 2005;Phillips and Ogeil, 2007), albeit with some exceptions (Breslin et al 1999;Sagoe et al 2017). There is some evidence that the effects of alcohol may be enhanced in people with gambling problems Ellery and Stewart 2014).…”
Section: Introductionmentioning
confidence: 99%
“…All participants were informed that they would receive either a low or high dose of alcohol (Hull and Bond 1986). We hoped that this approach would create an alcohol expectancy in both conditions; we note that more complex experimental designs are needed to evaluate the psychological effects of expectancy, which could also influence gambling behaviour (Breslin et al 1999;Sagoe et al 2017). To maintain blinding, a research nurse prepared all beverages, and the breathalyser display was masked, with the result stored in the device's memory for coding after the session.…”
Section: Methodsmentioning
confidence: 99%
“…In some studies, a moderately intoxicating dose of alcohol increased the speed and duration of play (Ellery et al 2005;Phillips and Ogeil 2007), increased risky wagering (Ellery et al 2005; Cronce and Corbin 2010;Ellery and Stewart 2014), and resulted in a more rapid depletion of available funds (Ellery et al 2005;Phillips and Ogeil 2007;Cronce and Corbin 2010). However, there have also been conflicting reports (Breslin et al 1999;Barrett et al 2015; Corbin and Cronce 2017;Sagoe et al 2017;Wagner et al 2018). For example, in a study by Barrett et al (2015), regular gamblers played an authentic EGM under four conditions, testing alcohol administration and nicotine stimulation in a 2 x 2 design.…”
Section: Introductionmentioning
confidence: 99%